Yüzyılların gerçeği ve mirası - Tanilli, Server, 1931-2011. (İstanbul İstanbul İstanbul İstanbul İstanbul)
6 c. (1. c. 544 s. ; 2. c. 465 s. ; 3. c. 540 s. ; 4. c. 524 s. ; 5. c. 570 s. ; 6. c. 656 s.)